The beast takes a bride - Long, Julie Anne (Romance author) (Long, Julie Anne (Romance author). Palace of rogues., 2024)
An estranged couple decide to fake their way through the London season to repair their good name ... but neither are prepared for the genuine sparks that begin flying between them.